Retrieval of cloud ice water path using SAPHIR on board Megha-Tropiques over the tropical ocean. Issue 7 (1st April 2017) - Piyush, Durgesh Nandan; Goyal, Jayesh; Srinivasan, J.
Highlights: Cloud Ice Water Path (IWP) retrieval from Megha-Tropiques SAPHIR. Concurrent observations from SAPHIR and TRMM-TMI are used in the retrieval. An Eigen value analysis based method is developed to retrieve IWP. The retrieval is compared with CloudSat, TMI, MSPPS and GPM-GMP IWP product. Abstract: The SAPHIR sensor onboard Megha-Tropiques (MT) measures the earth emitted radiation at frequencies near the water vapor absorption band. SAPHIR operates in six frequencies ranging from 183 ± 0.1 to 183 ± 11 GHz. These frequencies have been used to retrieve cloud ice water path (IWP) at a very high resolution. A method to retrieve IWP over the Indian ocean region is attempted in this study. The study is in two parts, in first part a radiative transfer based simulation is carried out to give an insight of using SAPHIR frequency channels for IWP retrieval, in the next part the real observations of SAPHIR and TRMM-TMI was used for IWP retrieval. The concurrent observations of SAPHIR brightness temperatures (Tbs) and TRMM TMI IWP were used in the development of the retrieval algorithm. An Eigen Vector analysis was done to identify weight of each channel in retrieving IWP; following this a two channel regression based algorithm was developed. The SAPHIR channels which are away from the water vapor absorption band were used to avoid possible water vapor contamination. When the retrieval is compared with independent test dataset, it gives a correlation of 0.80 and RMSE of 3.5%. SAPHIR derived IWP has been compared with other available global IWP products such as TMI, MSPPS, CloudSat and GPM-GMI qualitatively as well as quantitatively. PDF comparison of SAPHIR derived IWP found to have good agreement with CloudSat. Zonal mean comparison with recently launched GMI shows the strength of this algorithm.